The Pursuit of Happiness: 2011. - Fraad, Harriet (Tikkun (Duke University Press))
The article offers information on the Women's Liberation Movement of the 1960s and 1970s. It states that women's movement took momentum after the discrimination in pays, when women were paid less for the same job men were paid more. It mentions that one of the women's movement's largest mistakes was its failure to maintain its original insistence on class justice as well as gender justice.